How to form a nonprofit corporation : a step-by-step guide to forming a 501(c)(3) nonprofit in any state - Mancuso, Anthony; Nolo (Firm) (Berkeley, California : Nolo, 2015)
A guide that provides the forms and information needed to turn your group into a tax-exempt nonprofit. With this book, you can form a nonprofit corporation in any state and gain 501(c)(3) tax-exempt status with the IRS. Includes step-by-step instructions for both IRS Form 1023 and the new streamlined form 1023-EZ federal tax-exemption application for smaller nonprofits. Learn how to: choose a legal name; prepare articles of incorporation and bylaws for your nonprofit; obtain federal and state tax-exempt status; fill in minutes of the organizational meeting; establish a corporate records book.
Part. 1. How nonprofit corporations work : Is nonprofit incorporation right for you? : Is your group a nonprofit that can use this book? ; Benefits of the nonprofit corporation ; The disadvantages of going nonprofit ; Now nonprofits raise, spend, and make money ; Your path to nonprofit status ; Where should you incorporate? -- Legal rights and duties of incorporators, directors, officers, employees, and members : How many people are needed to form a nonprofit corporation? ; Incorporators and their role as promoters ; Directors ; Officers ; Employees ; Membership nonprofits -- Requirements for section 501(c)(3) tax exemption : Section 501(c)(3) organizational test ; Valid purposes under Section 501(c)(3) ; Other requirements for 501(c)(3) groups ; Information for specific questions about your group's activities -- Public charities and private foundations : The importance of public charity status ; How to qualify for public charity status ; Private foundations -- Other tax benefits and reporting requirements : Federal and state tax deductions for contributions ; Federal estate and gift tax exemptions ; Federal unrelated business income tax ; State corporate income tax exemptions ; Other state taxes ; State solicitation regulations ; State nonprofit corporate report requirements -- Part 2. Incorporating your nonprofit : Choose a name and file your articles of incorporation : View materials from your secretary of state ; Choose a corporate name ; Check name availability ; What to do when there's a name conflict ; Reserve your corporate name ; Perform a name search ; Protect your name ; Prepare your articles of incorporation ; File your articles of incorporation -- Prepare your bylaws : Choose a membership or nonmembership structure ; Purpose and scope of our bylaws ; Prepare your bylaws ; Prepare membership provisions -- Apply for your federal 501(c)(3) tax exemption : Getting started ; Do you need to file Form 1023? ; Prepare your tax exemption application ; Filling out the schedules ; Assemble and mail your application to the IRS ; What to expect from the IRS ; The federal determination letter -- Final steps in organizing your nonprofit corporation : Obtain state corporate income tax exemption ; Set up a corporate records book ; Prepare the minutes of your first board of directors meeting ; Place minutes and attachments in corporate records book ; Issue membership certificates ; File fictitious or assumed business name statement ; Apply for a federal nonprofit mailing permit ; Apply for property tax exemptions ; File an initial corporate report form ; Register with the Attorney General ; Comply with political reporting requirements ; Prepare assignments of leases and deeds ; File final papers for prior organization ; Notify others of your incorporation -- After your corporation is organized : Piercing the corporate veil: if you want to be treated like a corporation, it's best to act like one ; Federal corporate tax returns ; State corporate tax returns and reports ; Federal and state corporate employment taxes ; Employee income tax returns ; Sales tax forms and exemption for sales tax ; Licenses and permits ; Workers' compensation ; Private insurance coverage ; Dissolving a nonprofit corporation -- Lawyers and accountants : Lawyers ; Legal research ; Accountants and tax advice -- Appendixes : A. Using the interactive forms and other online material : Editing RTFs ; List of forms -- B. How to locate incorporation resources online : How to find your state's corporate filing office website ; How to find your state's tax office website ; How to find your state's corporation law lookup website -- C. Information and forms : Incorporation checklist ; Special nonprofit tax-exempt organizations ; Application for reservation of corporate name ; Articles of incorporation ; Articles filing letter ; Bylaws (including membership provisions and adoption of bylaws clause ; Waiver of notice and consent to holding of first meeting of board of directors ; Minutes of first meeting of board of directors ; IFS Form 1023-EZ: Streamlined application for recognition of exemption under Section 501 (c)(3) of the Internal Revenue Code ; IRS Form 1023: Application for recognition of exemption (with Notice 1382) Your path to nonprofit status ; Where should you incorporate? -- Legal rights and duties of incorporators, directors, officers, employees, and members : How many people are needed to form a nonprofit corporation? ; Incorporators and their role as promoters ; Directors ; Officers ; Employees ; Membership nonprofits -- Requirements for section 501(c)(3) tax exemption : Section 501(c)(3) organizational test ; Valid purposes under Section 501(c)(3) ; Other requirements for 501(c)(3) groups ; Information for specific questions about your group's activities -- Public charities and private foundations : The importance of public charity status ; How to qualify for public charity status ; Private foundations -- Other tax benefits and reporting requirements : Federal and state tax deductions for contributions ; Federal estate and gift tax exemptions ; Federal unrelated business income tax ; State corporate income tax exemptions ; Other state taxes ; State solicitation regulations ; State nonprofit corporate report requirements -- Part 2. Incorporating your nonprofit : Choose a name and file your articles of incorporation : View materials from your secretary of state ; Choose a corporate name ; Check name availability ; What to do when there's a name conflict ; Reserve your corporate name ; Perform a name search ; Protect your name ; Prepare your articles of incorporation ; File your articles of incorporation -- Prepare your bylaws : Choose a membership or nonmembership structure ; Purpose and scope of our bylaws ; Prepare your bylaws ; Prepare membership provisions -- Apply for your federal 501(c)(3) tax exemption : Getting started ; Do you need to file Form 1023? ; Prepare your tax exemption application ; Filling out the schedules ; Assemble and mail your application to the IRS ; What to expect from the IRS ; The federal determination letter -- Final steps in organizing your nonprofit corporation : Obtain state corporate income tax exemption ; Set up a corporate records book ; Prepare the minutes of your first board of directors meeting ; Place minutes and attachments in corporate records book ; Issue membership certificates ; File fictitious or assumed business name statement ; Apply for a federal nonprofit mailing permit ; Apply for property tax exemptions ; File an initial corporate report form ; Register with the Attorney General ; Comply with political reporting requirements ; Prepare assignments of leases and deeds ; File final papers for prior organization ; Notify others of your incorporation -- After your corporation is organized : Piercing the corporate veil: if you want to be treated like a corporation, it's best to act like one ; Federal corporate tax returns ; State corporate tax returns and reports ; Federal and state corporate employment taxes ; Employee income tax returns ; Sales tax forms and exemption for sales tax ; Licenses and permits ; Workers' compensation ; Private insurance coverage ; Dissolving a nonprofit corporation -- Lawyers and accountants : Lawyers ; Legal research ; Accountants and tax advice -- Appendixes : A. Using the interactive forms and other online material : Editing RTFs ; List of forms -- B. How to locate incorporation resources online : How to find your state's corporate filing office website ; How to find your state's tax office website ; How to find your state's corporation law lookup website -- C. Information and forms : Incorporation checklist ; Special nonprofit tax-exempt organizations ; Application for reservation of corporate name ; Articles of incorporation ; Articles filing letter ; Bylaws (including membership provisions and adoption of bylaws clause ; Waiver of notice and consent to holding of first meeting of board of
Subtitle from book cover.
"With downloadable forms"--Cover.
"Covers the new streamlined form 1023-EZ"--Cover.
Includes index.
Keywords: Nonprofit organizations -- Law and legislation -- United States -- Popular works; Incorporation -- United States -- Popular works